The Impact of Event in the Context and Response of Architectural Act - Alaskary, Abdullhussien Abdali (Iraqi Journal of Architecture and Planning, 2018)
The research philosophicallydeals with objects, about how the Architectural act represents many acts in the fact of context. The research problem is how the architectural act was responding to theevent that happened in thecontext. The research hypothesis is: there is a relationship between strategies of reading (explanation, interpretation, and deconstruction) and strategies of response (animation, renewal, and reform). The plan of the research includes two parts: first part includes knowledge framework about; event, response, and architectural act, second part includes analysis of terms and ideas of many architects. According to first part, the event, response, and architectural act is a philosophical concept, each of them can read another term, and became an event. The architectural act had a chance of physical event documentation in context, and it is one of main methods in society culture building. There are some conclusions, the main oneis that every architect has many readings of event and many responses at the same time, according to that there are verity in architectural acts. There is more than a singlestate between event reading and response kind because of the philosophical interpenetration between them. The contemporary Iraqi architecture fact needs to clearness, frankness and honesty in response of architects to build architectural act. Key Words:The event, context, response, architectural act, rehabilitation, renewal and reform